2011
DOI: 10.1530/joe-11-0129
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 deficiency attenuates induction of anti-TSH receptor antibodies and hyperthyroidism in a mouse Graves' model

Abstract: Experimental Graves'-like hyperthyroidism can be induced in susceptible mouse strains by repetitive immunizations with recombinant adenovirus expressing the human full-length TSH receptor (TSHR) or its A-subunit. Previous studies have shown that splenocytes from immunized mice produce interferon (IFN)-g and interleukin (IL) 10 in response to antigen stimulation in an in vitro T cell recall assay. Although IFN-g is now well known to be essential for disease induction, the role(s) played by IL10 are unknown. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…In addition, TNF-α, IL-6, IL-8 IL-10 and IL-13 have already been described for various involvements in TAO. These include (i) stimulation of the glycosaminoglycan production in vitro in ocular fibroblast for TNF-α 30 , 31 , (ii) secretion by orbital fibroblasts under the stimulation of TSHR antibodies or prostaglandin E2 for IL-6 32 34 , (iii) expression by fibrocytes that can induce the infiltration of inflammatory cells and subsequent tissue remodelling for IL-8 35 and the steroid treatment which decreases its expression level for IL-8 22 and (iv) regulation of both T and B-cells functions for IL-10 36 . Finally, for all of them, genetic polymorphism of their gene in relation with TAO have been identified in different populations 21 , 37 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TNF-α, IL-6, IL-8 IL-10 and IL-13 have already been described for various involvements in TAO. These include (i) stimulation of the glycosaminoglycan production in vitro in ocular fibroblast for TNF-α 30 , 31 , (ii) secretion by orbital fibroblasts under the stimulation of TSHR antibodies or prostaglandin E2 for IL-6 32 34 , (iii) expression by fibrocytes that can induce the infiltration of inflammatory cells and subsequent tissue remodelling for IL-8 35 and the steroid treatment which decreases its expression level for IL-8 22 and (iv) regulation of both T and B-cells functions for IL-10 36 . Finally, for all of them, genetic polymorphism of their gene in relation with TAO have been identified in different populations 21 , 37 44 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it inhibits the activities of nuclear factor-κB and alters the JAK-STAT signaling pathway ( 16 ). A previous study on a murine model indicated that IL-10 deficiency reduces the induction of anti-thyroid stimulating hormone receptor antibodies; thus, IL-10 plays an important role in the development of GD in mice ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…That is the main reason why the two autoimmune thyroiditis have different clinical pictures. It is decided by the characteristics of autoantibodies [82]. Like SLE, anti-nuclear antibodies can be detected in autoimmune thyroiditis, especially in Grave's disease.…”
Section: Thαβ Immunological Pathway Related With Grave's Diseasementioning
confidence: 99%